Government debt and economic growth / Ng Cai Xin - Ng , Cai Xin (2020)
The level of Malaysia government debt have been hiking in recent years which leads to controversies regarding the sustainability of the debt level. The question that borrowings will stimulate or inhibit the economy remains as an important issue to be addressed. This paper examines the impact of government debt on economic growth in Malaysia. Utilizing the macroeconomic data between 1970 and 2018, we first apply an autoregressive distributed lag (ARDL) framework to examine the relationship between government debt and economic growth. The short term and long term relationship as well as cointegrating relationship between government debt and economic growth were examined. Next, quantile regression was employed to investigate the impact of government debt on economic growth of Malaysia at different stages of development. The most important finding of this paper is the negative relationship between government debt and economic growth in short term and long term. The results contradict the previous evidences showing the nonlinear relationship between government debt but are consistent with the existing literature stating the negative impact of government debt on economic growth. Besides, the results of quantile regression show that the negative impact of government debt on economic growth become significant starting at quantile 0.9. These findings indicate that the government should engage in fiscal consolidation to ensure sustainable economic growth.